A study on lumay and its relation to human pheromones - Balanlay, Gina Rose P.; Ganzo, Bikki A. (2003)
Countless stories have been told about lovelorn men painstakingly searching long in history for the impeccable love potion. The discovery of the human pheromones seems to have provided them the solution. Numerous studies have been done on human pheromones, and results seem to lead towards one particular direction--pheromones, an effective sex-attractant.